เรือนลาวแง้วที่บ้านตาลเสี้ยน สระบุรี - ปาณินท์ อรศิริ (NAJUA: Architecture, Design and Built Environment, 2017)
“ลาวแง้ว” คือชื่อที่เรียกขานชาวลาวที่โยกย้ายถิ่นฐานออกจากพื้นที่รอบนอกของเวียงจันทน์ มาตั้งถิ่นฐานอยู่ในพื้นที่ภาคกลางของประเทศไทย ขณะที่ลาวเวียง คือ กลุ่มลาวที่มีถิ่นฐานดั้งเดิมอยู่ในเมืองเวียงจันทน์ จากการศึกษาเรือนลาวในพื้นที่ต่างๆ ทั้งในลาวและในไทย พบว่ารูปลักษณ์ของเรือนในแต่ละพื้นที่มีความแตกต่างกัน การศึกษานี้ต้องการศึกษาเพื่อสืบค้นว่า เรือนลาวแง้วในพื้นที่บ้านตาลเสี้ยน ตำบลหนองแก อำเภอพระพุทธบาท จังหวัดสระบุรี ซึ่งมีอายุการตั้งถิ่นฐานกว่า 200 ปี มีรูปลักษณ์และผังพื้นเรือนแบบเดียวกับเรือนในพื้นที่ต้นกำเนิดหรือไม่ อิทธิพลของวัฒนธรรมหลักของไทยครอบคุลมรูปลักษณ์ของเรือนหรือไม่ อย่างไร จากการศึกษาพบว่า ทั้งเรือนลาวเวียงและลาวแง้วในไทยต่างได้รับการถ่ายทอดรูปแบบแผนผังเรือนจากเรือนลาวเวียงจันทน์ แต่มีรูปลักษณ์แปรไปตามบริบทของไทยในแต่ละพื้นที่ สำหรับเรือนลาวแง้วในบ้านตาลเสี้ยนมีอิทธิพลของรูปทรงเรือนไทยประเพณีภาคกลางครอบคลุมรูปลักษณ์ทางกายภาพอย่างชัดเจนในลักษณะเรือนไทยประเพณีจั่วแฝด แต่ยังธำรงเอกลักษณ์ของการอยู่และลำดับการเข้าถึงพื้นที่ภายในแบบลาวเวียงจันทน์อย่างชัดเจน รูปลักษณ์ของเรือนไทยประเพณีแผ่คลุมรูปลักษณ์ทางกายภาพของเรือนลาวแง้วมากกว่าเรือนลาวเวียงในจังหวัดราชบุรี Lao Ngaew Houses at Baan-Tan-Siane in Saraburi Ornsiri Panin Faculty of Architecture, Kasetsart University Lao Ngaew is the name accorded to Lao ethnic group of people who migrated 200 years ago from the outskirts of Vientiane to the Central Region of Thailand. While Lao Vieng refers to those that have their origin in Vientiane. From the study of Lao vernacular houses both in the Lao PDR and in Thailand, it was found that there are diverse types to Lao houses. This study aims to find out whether the Lao Ngaew vernacular houses in Ban-Tan-Siane, Nong Kae Sub-district of Praputtabat District in Saraburi Province, still have the same characteristics as those at the place of origin, and whether Thai culture had any influence on their appearances at all. The study found that both Lao Vieng and Lao Ngaew house plans in Thailand were strongly influenced by the old Vientiane house plan. The house form and appearance varied with their contexts. Lao Ngaew houses in Ban-Tan-Siane were predominantly influenced by the traditional Thai houses with the overall characteristic being the traditional Thai style twin-gable. However, the spatial organization of spaces in their house plans still remained basically the same. Thus traditional Thai house character had more influence on the Lao Ngaew houses than on the Lao Vieng houses.